2015
DOI: 10.3130/jaabe.14.657
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Hydration Heat Control of Mass Concrete by Vertical Pipe Cooling Method

Abstract: Thermal cracking of slender mass concrete in attached walls, retaining walls and bridge towers, is controlled by mainly using low heat cement and the control joint. However, it is impossible to control thermal cracks perfectly because the external restraint is largely in these mass concrete members. In this study, to control the thermal cracking of slender massive concrete structures, a new pipe cooling method, which is the vertical pipe cooling method, was developed and a mock-up of a wall-type mass concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…The function was assigned to the corresponding units as shown in Figure 12. The maximum adiabatic temperature rise K of mass concrete was calculated by Equation (10) and was obtained as 47.9˝C. It should be emphasized that the heat generated by the concrete can be calculated by Equations (10) and (13), and the calculation results are in agreement with the adiabatic calorimetry test results [21].…”
Section: Convective Heat Transfer Coefficient Function For the Side Ssupporting
confidence: 71%
See 1 more Smart Citation
“…The function was assigned to the corresponding units as shown in Figure 12. The maximum adiabatic temperature rise K of mass concrete was calculated by Equation (10) and was obtained as 47.9˝C. It should be emphasized that the heat generated by the concrete can be calculated by Equations (10) and (13), and the calculation results are in agreement with the adiabatic calorimetry test results [21].…”
Section: Convective Heat Transfer Coefficient Function For the Side Ssupporting
confidence: 71%
“…Seo et al [10] developed a vertical pipe cooling method and tested it in a wall-type mass concrete specimen to validate the method. The experimental result showed that the temperature of the concrete specimen with the vertical pipe cooling system was 8-14˝C lower than that of the control specimen without the vertical pipe cooling system.…”
Section: Introductionmentioning
confidence: 99%
“…Using cooling pipe is an important measure to control the temperature of mass concrete and prevent cracking. Engineering experience [1][2][3][4][5][6][7][8][9][10] has shown that the embedded cooling pipe in the concrete can effectively reduce the temperature peak inside the structure. However, the simulation of the temperature field of massive concrete with embedded cooling pipes is computationally intensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The data have used for design and placement or structural function. A kind of concrete characteristic is concrete strength and heat hydration [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Concrete strength is an indicator of concrete quality, and heat hydration is an indicator of period time hydration reaction and setting time.…”
Section: Introductionmentioning
confidence: 99%
“…And the temperature will increase due to the reaction speed of hydration and exothermic process. The heat will increase without external temperature influence [8,[10][11][12]17,18,22].…”
Section: Introductionmentioning
confidence: 99%